2020
DOI: 10.1042/bsr20200115
|View full text |Cite
|
Sign up to set email alerts
|

Green nanogold activity in experimental breast carcinoma in vivo

Abstract: Background: Over the past few years, fabrication of nanoparticles (NPs) has been deployed widely in technologies and many concerns have emerged about the hazardous effect on human health after NPs exposure. Objective: Green synthesis of gold NPs (AuNPs) and assessment of their activity in 7,12-dimethylbenz(a)anthracene (DMBA)-induced breast cancer mouse model. Methods: Chloroauric acid (HAuCl4) was used in formation of AuNPs with the help of Curcuma longa as aqueous reducing extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The results of the study revealed that most AuNPs prepared were spherical, with variations in size (in the range of 10–30 nm). The group treated with AuNPs after breast cancer induction showed degenerative tumor lesions in the breast and lymph nodes [ 54 ].…”
Section: Cancermentioning
confidence: 99%
“…The results of the study revealed that most AuNPs prepared were spherical, with variations in size (in the range of 10–30 nm). The group treated with AuNPs after breast cancer induction showed degenerative tumor lesions in the breast and lymph nodes [ 54 ].…”
Section: Cancermentioning
confidence: 99%
“…Nanogold has recently demonstrated its ability to enter cancer cells and accumulate within them. Thus, NG has been shown to easily infiltrate the tumor vasculature and persist in tumors, resulting in their prolonged survival, which raised their concentration and ultimately resulted in tumor cell damage [ 30 , 42 ]. It can also bind to other medications and chemicals, transporting them within tumor cells [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is non-toxic, and the kidneys can eliminate it [ 45 ]. Hendi et al 2020 found that animals injected with NG (1–9 nm) had smaller tumors and a greater survival rate when compared to untreated control mice [ 30 ]. Many studies have demonstrated that NG may have tremendous potential for people suffering from metastases following breast cancer [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transplantation of human tumor fragments into immunocompromised mice has been reported by Hoffman et al [ 184 ]. PDXs are very attractive models due to the preservation of many relevant characteristics of the primary human tumor, such as growth kinetics, histological characteristics, and behavioral characteristics (invasiveness and metastatic capacity), regardless of the ability to respond to tumor therapy [ 185 , 186 , 187 , 188 , 189 , 190 ]. Moreover, these models have had an important industrial impact, and they are the choice for translational research.…”
Section: Cancer Evaluation Modelsmentioning
confidence: 99%